2013
DOI: 10.1098/rsbl.2012.0951
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-localization of type-IV collagen in the blood-gas barrier and the epithelial–epithelial cell connections of the avian lung

Abstract: The terminal respiratory units of the gas exchange tissue of the avian lung, the air capillaries (ACs) and the blood capillaries (BCs), are small and rigid: the basis of this mechanical feature has been highly contentious. Because the strength of the blood-gas barrier (BGB) of the mammalian lung has been attributed to the presence of type-IV collagen (T-IVc), localization of T-IVc in the basement membranes (BM) of the BGB and the epithelial-epithelial cell connections (E-ECCs) of the exchange tissue of the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…After comparing the strengths (stress tolerance) of the blood capillaries in the rabbit lungs, the dog lungs, and the horse lungs, Birks et al observed that stress failure may correlate with the thickness of the BGB (Birks et al, 1994), a property consistent with Laplace's relationship which states that wall stress is proportional to capillary radius but inversely proportional to wall thickness. We have demonstrated collagen fibers in the basement membrane of the BGB and the EECCs of the lung of the chicken (Maina et al, 2010) and immunolocalized type-IV collagen (Jimoh and Maina, 2013), a protein family of triple helical isoforms that form strong two-dimensional planar network of fibers (Timpl, 1989; Hudson et al, 1993; West, 2009), in the exchange tissue of the lung of the domestic fowl. The strength of the BGB of the mammalian lung has been attributed to presence of type-IV collagen in the basement membrane (Crouch et al, 1997; West and Mathieu-Costello, 1999; Maina and West, 2005; West, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…After comparing the strengths (stress tolerance) of the blood capillaries in the rabbit lungs, the dog lungs, and the horse lungs, Birks et al observed that stress failure may correlate with the thickness of the BGB (Birks et al, 1994), a property consistent with Laplace's relationship which states that wall stress is proportional to capillary radius but inversely proportional to wall thickness. We have demonstrated collagen fibers in the basement membrane of the BGB and the EECCs of the lung of the chicken (Maina et al, 2010) and immunolocalized type-IV collagen (Jimoh and Maina, 2013), a protein family of triple helical isoforms that form strong two-dimensional planar network of fibers (Timpl, 1989; Hudson et al, 1993; West, 2009), in the exchange tissue of the lung of the domestic fowl. The strength of the BGB of the mammalian lung has been attributed to presence of type-IV collagen in the basement membrane (Crouch et al, 1997; West and Mathieu-Costello, 1999; Maina and West, 2005; West, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A–D) that strengthens the respiratory units by the property of interdependence in which collapse of individual respiratory units is resisted by a tethering effect to others via the connective tissue elements (Hlastala & Berger, ; West, Watson & Fu, ); the thickening of epithelial–epithelial cell connections and accumulation of extracellular matrix at the triangular sites (Fig. A–C) that modulates the hoop stress in the walls of the blood capillaries, reinforcing them (Maina & West, ; West et al, ); and the existence of abundant, intricately arranged, and diffuse collagen fibres in the exchange tissue, blood–gas barrier and epithelial–epithelial cell connections (Maina, Jimoh & Hosie, ; Jimoh & Maina, ) (Figs D–F, ).…”
Section: Structural Features Of the Lung And Air And Blood Capillariesmentioning
confidence: 99%
“…The location and spatial distribution of collagen fibres and smooth muscle tissue in the chicken lung were studied by Maina et al (2010 a ) and Jimoh & Maina () (Figs and A) and based on these features the implied forces in a parabronchus were modelled (Fig. B–D).…”
Section: Structural Features Of the Lung And Air And Blood Capillariesmentioning
confidence: 99%
“…Further research is needed to explain it. The immunological demonstration of presence of the exceptionally strong type IV collagen in the basement membrane of the BGB and the E‐ECCs of the exchange tissue of the avian lung by Jimoh and Maina () is the first direct and unequivocal demonstration of one of the causes of the strength of the blood capillaries and the air capillaries. With the new understanding of the morphologies of the ACs and BCs, the terms “air capillary” and “blood capillary” are inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…13 and 15); (c) presence of a trilamilar substance (TLS), a type of surfactant which is unique to the avian lung (Tyler and Pangborn, ; Petrik and Riedel, ; Scheuermann et al, ) and which serves as an intricate intercapillary anastomosing skeletal supporting system (Klika et al, ); (d) possible existence of a tensegrity (tension integrity) system (Fuller, ; Ingber, ) which in the compact and rigid lung (Maina, ), tension and compression forces are efficiently absorbed and dissipated by well‐organized connective tissue elements like smooth muscle, collagen‐, and elastic tissue fibers (Maina, ; Maina et al, ) (Figs. 22–25), and; (e) presence of the strong type‐IV collagen (Stromberg and Wiederhielm, ; Maina and West, ; Jimoh and Maina, ) in the basement membranes of the BGB and the E‐ECCs (Maina and Jimoh, in press) (Figs. 25).…”
Section: Putative Bases Of the Strengths Of The Air‐ And The Blood Camentioning
confidence: 99%